Impact of Internet Financial Reporting on Stock Returns and Trading Volume of Banking Stocks - Rahmisyari Rahmisyari (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study studies and determines the impact of financial reporting on the Internet on stock returns and trading volume. This study is quantitative—a retraction of research ideas backed by previous investigations employing the same variables and Signal theory. Internet Financial Reporting, Stock Returns, and Trading Volume are research variables. The population for this study consists of 43 banking companies listed on the Indonesia Stock Exchange for the period 2021. This study used a purposive sampling method to obtain a total sample size of 29 banks. Secondary data in financial statements are processed and utilized Using Eviews 12, the analytical strategy comprises descriptive statistical analysis and a panel data regression test. The results indicate that Internet Financial Reporting has a positive but negligible impact on the stock returns and trading volume of Indonesia Stock Exchange-listed banking companies. Internet Financial Reporting has not been a factor in determining whether investors are happy with the stock return data. The minimal influence of Internet Financial Reporting on Stock Returns is due to the inability of the company's Internet Financial Reporting value to offer investors complete information about stock returns before making investment decisions in banking companies. This indicates that Internet Financial Reporting has not become a factor in determining whether investors are satisfied with the information they receive regarding Stock Trading Volume. The negligible impact of Internet Financial Reporting on Stock Trading Volume is due to the inability of the company's Internet Financial Reporting value to offer investors accurate information regarding Stock Trading Volume before making investment decisions in banking firms.